القيم الأخلاقية بين الحرية والضرورة عند باروخ إسبينوزا - مسيكة، محمد الصغير Masikah, Mohammed Alsaghir; لعموري، شهيدة Laamouri, Shahidah (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2021)
تعتبر مسألة الحرية من بين أهم المسائل الفلسفية التي تعبر عن الوجود الإنساني، لأنها مرتبطة بالفعل الوجودي الذي يمارسه الإنسان في حياته، والذي يثبت من خلاله قيمته كإنسان وكينونته كموجود باحث عن أجوبة لتساؤلاته. لقد تعددت البحوث الفلسفية حول الحرية بدءًا من المفهوم وصولاً إلى التنظير للحرية على يد مفكرين وفلاسفة أمثال؛ باروخ إسبينوزا (Baruch Spinoza)) (1632- 1677م)، الذي حاول بناء فلسفته الأخلاقية داخل نسق تحكمه الحتمية الخاضعة لنظام الطبيعة الذي يعتبر الإنسان جزء منه وخاضع هو أيضا لهذا النظام الذي يحكم في تصرفات وانفعالات البشر الأساسية. وما دامت سائر الأفعال في نظر إسبينوزا تسير وفق حتمية ثابتة، بحيث يمكن النظر إلى الإنسان على أنه آلة مفكرة، تخضع في تصرفاتها لنظام الكون الشامل، ولا يتمتع بإرادة حرة.
The issue of freedom is considered one of the most important philosophical issues that express human existence, because it is related to the existential act that man practices in his life, through which he establishes his value as a person and his being as an existence seeking answers to his questions. Philosophical research on freedom has varied from the concept to the theorizing of freedom at the hands of thinkers and philosophers such as: Baruch Spinoza (1632-1677 AD), who tried to build his moral philosophy within a system of determinism governed by the system of nature that man considers a part of and subject to himself. Also for this system that controls the basic human actions and emotions. As long as all other actions are in Spinoza's view they proceed according to a fixed imperative, so that man can be seen as a thinking machine, subject in its actions to the system of the universal universe, and not having free will. Then we will find no justification for the moral penalty within this system governed by absolute determinism, and there is no room for freedom in it except within the framework of what this general order requires.
Keywords: الفكر الفلسفي -- سبينوزان، باروخ -- القيم الأخلاقية -- الحرية